Un ritratto di Commodo nelle collezioni del Castello del Buonconsiglio (Trento) - Mosca, Annapaola (Römische Mitteilungen, 2024)
Presented here is a portrait of Commodus preserved in Trento in the Buonconsiglio Castle (monumenti e collezioni provinciali), where it is currently exhibited in the room named “Torrione da basso”. Considered a portrait of Marcus Aurelius or of an ‘ideal emperor’ of the second-third centuries AD, the portrait-bust had been judged to be a work of the late 16th or 17th century. The identification of the head with that of the Roman emperor Commodus had already been proposed in a short note by Klaus Fittschen, who argued that it was an authentic portrait, inserted into a modern bust. Until now this portrait has never been studied in detail and suffered from a lack of secure provenance details. Here we trace the last two centuries of the history of the statue, thereby confirming that it is indeed a portrait of the young Commodus. We explain how it ended up in the collections of the Buonconsiglio Castle. Our goal in this is to make this portrait known and valued.